Principal’s Academic Supervision for Improvement of Teacher’s Performance - Pratiwi, Dinny Hariyati (PPSDP International Journal of Education, 2024)
This research was conducted with a quantitative approach and used a survey method. The aim of this research is to prove that there is a significant relationship between principal supervision and increased teacher’s performance. The respondents in this research were 61 teachers at SMP Negeri 1 Palembang. This instrument was created as a questionnaire using a Likert scale. Simple regression analysis is used to test the hypothesis. This study found that there was a relationship between principal supervision and teacher’s performance improvement at SMP Negeri 1 Palembang with a t value of 3.86 with a regression coefficient of 0.39. The t value > of the coefficient. Reg = 0.39. This research shows that an increase in principal supervision will follow an increase in teacher’s performance, and vice versa, a decrease in principal supervision will follow a decline in teacher’s performance. Therefore, school principals are advised to improve their supervisory abilities so that they can provide better services in teaching and developing teacher talent.